Respondents versus informants method of data collection: implication for business research - Hassan, Arif; Sinha, R B N (Human Resource Management Academic Research Society (HRMARS), 2014)
The present study juxtaposes the prevailing method of individual respondents’ self-ratings with their ratings of how people in the society think, feel, and behave in order to identify a culturally sensitive method to explore social reality. A sample of 100 adults from India and 127 university students from Malaysia rated predominantly positive and negative description of beliefs, values and preferences twice-first for the people residing around them and then for themselves. They also rated themselves on a scale of social desirability. The findings confirmed that the respondents attributed negative cognitions (beliefs, values and preferences) to the people more than themselves. They attributed predominantly positive beliefs, values and preferences to themselves and people, although a shade more to themselves. The social desirability orientation was meaningfully related to respondents’ self but not to people’s related perceptions. The findings thus favoured the use of respondents in informants’ role of judging people’s cognitions of social reality.